(untitled) (Research, Society and Development, 2024)
Objective: Explain how the decline in vaccine coverage in the country is related to the resurgence of cases. Methods: Analytical and observational study using DATASUS data, comparing the periods from 2012 to 2022 for the vaccines: VIP, TV, and FA, with filters for Year, Immunization, Vaccine Coverage, and Confirmed Cases. Results: None of the studied vaccines reached the vaccination target during the analyzed period. Low Polio vaccination can lead to its resurgence. Yellow Fever vaccination rates below recommended levels are linked to outbreaks in 2016 and 2018. The return of Measles virus circulation in 2018 is also justified by vaccine decline and the entry of unvaccinated immigrants into the territory. Conclusion: There is a observed decline in vaccine coverage and a resurgence of Measles and Yellow Fever viral circulation, posing a risk to public health, overburdening the public health system, and increasing hospitalization and mortality rates.